Morphological characteristics of primary diffuse large B-cell lymphoma of the central nervous system. - I. S. Shpon‘ka; P. O. Grytsenko; T. V. Shinkarenko (Морфологія, 2016)
Background. Primary central nervous system lymphoma is aggressive tumors with a poor prognosis, morphologically mostly diffuse large B-cell lymphoma (95%), which are included to separate nosological form - primary central nervous system diffuse large B-cell lymphoma. In recent decades, it is known these tumors have increasing incidence rate. Objective. Here we were determining the histological and immunohistochemical features of primary central nervous system diffuse large B-cell lymphoma for improving the morphologic diagnostics of this tumors type and developing predictive and prognostic factors. Methods. The study included 10 cases of primary central nervous system diffuse large B-cell lymphoma with tissue material received with biopsy or operation. The wide range of imunohistochemical stains (Ki-67, CD3, CD10, CD20, CD30, CD79α, BCL2, BCL6, GFAP) was used for detection of morphological characteristics in all cases. Results. We observed histological features of diffuse large B-cell lymphoma (diffuse or perivascular growth pattern of large round cells with frequently mitotic figures, apoptotic bodies and necrotic areas). In all cases we revealed CD20+ and CD79α+ (markers of B-lymphocytic differentiation) tumor cells. Expression of BCL6 and BCL2 was present in 80 and 60 percents of cases respectively. In addition some cases show CD30 or/and CD10 – immunoreactivity. Range of proliferative activity (Ki-67) was from 52 to 94%. Conclusion. The histological and immunohistochemical methods are useful for diagnosis of diffuse large B-cell lymphoma in tissues received with biopsy or brain resection. The typical features of diffuse large B-cell lymphoma are credible for diagnosis with using immunohistochemical status of neoplastic cells (CD20+, CD79α+, CD10 –, CD30–, BCL6+, BCL2+). The level of Ki-67 expression has potential important prognostic value due to its variability.